Transparent conductive film, high-light-transmittance dimming film and preparation method of high-light-transmittance dimming film

By forming a conductive layer of modified carbon nanotubes on the surface of the transparent PVB film, the problems of high resistivity and poor flexibility of existing dimming film materials are solved, and a transparent conductive film with high light transmittance and flexibility is achieved, which is suitable for flexible applications. Production of switchable film.

CN119355993APending Publication Date: 2025-01-24FOSHAN CHENWEI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411810754.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The conductive film materials of existing dimming films, such as ITO films, have high resistivity, greater resistance after the screen size increases, increased processing difficulty, and lack flexibility, and cannot adapt to automotive glass with a large curvature.

Method used

The transparent PVB membrane is used as a substrate, and the conductive layer of the modified carbon nanotuba is formed on its surface. Flexible transparent conductive film.

Benefits of technology

It realizes excellent conductivity and high light transparency, and has high flexibility. It is suitable for making a flexible lighting film. The production efficiency is higher and the cost is lower.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355993A_ABST
    Figure CN119355993A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of dimming films, and particularly relates to a transparent conductive film, a high-light-transmittance dimming film and a preparation method thereof, the transparent conductive film comprises a transparent PVB film, a conductive layer formed by modified carbon nanotubes grafted on the surface of the transparent PVB film, and the modified carbon nanotubes grafted by N-chloroformyl-2-imidazolidinone, the flexible light-adjusting film has excellent conductivity, high light transmittance and high flexibility, and is suitable for manufacturing the flexible light-adjusting film; the dimming film has relatively low driving voltage, good fog-state shielding performance and relatively high transparent-state transparency. Wherein the obtained positive dimming film is in a fog state when being not electrified and is in a transparent state when being electrified, and is suitable for places requiring long-time shading, such as a skylight of an automobile; micron-sized grooves distributed in parallel are formed in the surface of the transparent conductive film through the micro-nano imprinting copying technology, alignment is conducted on the initial state of liquid crystal molecules, and the liquid crystal molecules are in a transparent state when not powered on and in a fog state when powered on.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of dimming films, and in particular relates to a transparent conductive film, a high-light-transmittance dimming film and a preparation method thereof. Background Art

[0002] Dimming film, also known as PDLC (polymer dispersed liquid crystal) film, electric control film, atomizing film or electronic curtain, is mainly composed of two transparent conductive films with liquid crystal / polymer mixed materials injected between them, and synthesized by precision coating. Dimming film has a wide range of applications, including but not limited to being used on the windows of cars and high-speed trains. Dimming film includes positive dimming film and reverse dimming film. Positive dimming film is in an opaque or foggy state when not powered on, and in a transparent state when powered on; while reverse dimming film is in a transparent state when not powered on, and in an opaque or foggy state when powered on. Among them, the transmittance, power consumption performance, flexibility and other indicators of the dimming film in the foggy and transparent states are mainly affected by the transparent conductive film. Most of the existing dimming films use ITO film as the transparent conductive film, and the resistivity of ITO film is relatively high. As the screen size increases, the resistance will continue to increase, affecting the screen brightness and sensor responsiveness. In addition, ITO film is relatively brittle, and the difficulty of processing will increase as the size increases. Moreover, due to its lack of flexibility and difficulty in bending, it is not suitable for automotive glass with large curvature.

[0003] There are some alternatives to ITO film, such as nano silver wire conductive film and metal grid transparent PVB film. However, the preparation process is relatively complex and requires precise control of parameters such as the size, shape and distribution of the nano silver wire. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a transparent conductive film, a high-transmittance dimming film and a preparation method thereof, which have excellent conductivity, high light transmittance and flexibility, higher production efficiency and lower cost.

[0005] The invention provides a transparent conductive film, comprising a transparent PVB film and a conductive layer formed by modified carbon nanotubes grafted on the surface of the transparent PVB film.

[0006] Optionally, the modified carbon nanotubes are products of acylation reaction between amino carbon nanotubes and N-chloroformyl-2-imidazolidinone.

[0007] Optionally, the method for preparing the modified carbon nanotubes comprises the following steps:

[0008] The raw materials are calculated by weight, and 50-110 parts of amino carbon nanotubes, 0.5-1 part of DMAP, and 10-50 parts of triethylamine are added to an organic solvent and mixed. 10-60 parts of N-chloroformyl-2-imidazolidinone are added under continuous stirring. After the reaction is complete, the modified carbon nanotubes are obtained by filtering, washing, and drying.

[0009] Optionally, the amino-modified carbon nanotubes have a diameter of 1 to 2 nm and a length of 5 to 30 μm.

[0010] Optionally, the organic solvent is at least one of dichloromethane, DMSO and DMF.

[0011] Optionally, the thickness of the conductive layer in the transparent conductive film is 10-55 nm.

[0012] A method for preparing a transparent conductive film comprises the following steps:

[0013] Raw materials are measured in parts by weight;

[0014] 5-15 parts of modified carbon nanotubes, 0.1-1 parts of aluminum chloride, 0.1-1 parts of acetic acid, and 0.1-1 parts of sodium dodecyl sulfate are stirred in water to form a suspension;

[0015] Firstly, a transparent PVB film is attached to a substrate, and then both are immersed in the above suspension, irradiated with ultraviolet light for 10-60 minutes, and reacted under microwave for 2-10 hours. Then, the transparent PVB film and the substrate are taken out, rinsed with water, and a transparent conductive film is obtained; the substrate is a glass plate or a PMMA plate.

[0016] A high-transmittance dimming film comprises a transparent conductive film, a polymer dispersed liquid crystal layer and a transparent conductive film which are stacked in sequence.

[0017] A high-transmittance dimming film comprises a transparent conductive film, a horizontal alignment layer, a polymer dispersed liquid crystal layer, a horizontal alignment layer and a transparent conductive film which are stacked in sequence.

[0018] A method for preparing a high-transmittance dimming film, the method comprising the following steps:

[0019] A polymer dispersed liquid crystal is coated on one side of a transparent conductive film having a conductive layer, and then another side of a transparent conductive film having a conductive layer is covered on the polymer dispersed liquid crystal, and after curing, a high light transmittance dimming film is obtained; or

[0020] The preparation method comprises the following steps:

[0021] A micro-nano imprint copying technique is used on one side of the transparent conductive film having a conductive layer to form parallel distributed micron-scale grooves to obtain a horizontal alignment layer, and then a polymer dispersed liquid crystal is coated;

[0022] The side of the other transparent conductive film with a conductive layer is also copied by micro-nano imprinting technology to form horizontal nano-scale grooves to obtain a horizontal alignment layer, which is then covered on the polymer dispersed liquid crystal and cured to obtain a high-transmittance dimming film;

[0023] The method for preparing the horizontal alignment layer comprises the following steps:

[0024] Place the conductive layer side of the transparent conductive film upwards, align the micro-nano imprint template with the transparent conductive film and place it in the imprinting machine, perform imprinting at 60-70°C and 2-6MPa pressure, maintain the pressure for 5-10 minutes, cool it down, demold it, and obtain a horizontal alignment layer.

[0025] Optionally, the thickness of the polymer dispersed liquid crystal layer is 20 to 35 μm.

[0026] The beneficial effects of the present invention are that the transparent conductive film provided by the present invention, the modified carbon nanotubes obtained by grafting N-chloroformyl-2-imidazolidone, have excellent conductivity and high light transmittance, and after being bent 500 times, the conductivity does not change significantly, has high flexibility, and is suitable for making flexible dimming films. The chemical grafting method for forming a conductive layer also has lower condition requirements, higher efficiency and lower cost than the vapor phase lamination method.

[0027] The dimming film provided by the present invention has a lower driving voltage, good fog-state shielding property, and higher transparency in a transparent state. Among them, the obtained positive dimming film is foggy when not powered on and transparent when powered on, and is suitable for places that require long-term light shielding, such as the sunroof of a car; the obtained reverse dimming film uses micro-nano imprint copying technology to form parallel micron-level grooves on the surface of the transparent conductive film, aligns the initial state of the liquid crystal molecules, and is transparent when not powered on and foggy when powered on. The precision of the micron-level grooves made by the micro-nano imprint copying technology is easier to control, and the uniformity is also higher. The obtained pressed film can be reused, and a pressed film with a certain curvature can be used to make a dimming film with a designed curvature. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is an infrared spectrum curve diagram of the modified carbon nanotubes and transparent conductive film of Example 1;

[0029] In the figure: A, infrared spectrum of amino carbon nanotubes; B, infrared spectrum of modified carbon nanotubes; C, infrared spectrum of transparent conductive film. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0031] Example 1

[0032] Preparation of transparent conductive film:

[0033] The raw materials are calculated by weight: 60 parts of amino carbon nanotubes, 0.5 parts of DMAP, and 20 parts of triethylamine are added to dichloromethane and mixed, and 20 parts of N-chloroformyl-2-imidazolidinone is added dropwise under continuous stirring. The mixture is reacted for 2 hours, filtered, washed with ethanol 3 times, washed with water 3 times, and dried under vacuum at 50°C for 5 hours to obtain modified carbon nanotubes;

[0034] 5 parts of modified carbon nanotubes, 0.1 parts of aluminum chloride, 0.5 parts of acetic acid, and 0.5 parts of sodium dodecyl sulfate were stirred in purified water for 5 minutes to form a suspension;

[0035] A transparent PVB film is then attached to a glass plate and then immersed in the above suspension. The thickness of the suspension above the transparent PVB film is 2 mm. The ultraviolet light intensity is 5000 μW / cm2, the irradiation time is 30 min, and the reaction is carried out for 3 hours under the action of microwaves. The temperature is controlled at 40-55°C. After that, the transparent PVB film is taken out and rinsed with water to obtain a transparent conductive film. Among them, the thickness of the conductive layer in the transparent conductive film is 23 nm.

[0036] like Figure 1 As shown in the figure, it can be seen that the infrared characteristic absorption peak of amino carbon nanotubes is at 3460cm -1 The NH vibration absorption peak appears at 1721 cm -1 1665cm -1 Two C=O contraction vibration peaks appeared at 1721 cm-1, which are the C=O of keto carbonyl and amide groups, indicating that N-chloroformyl-2-imidazolidinone was successfully grafted onto the amino carbon nanotubes. The infrared characteristic absorption peak of the transparent conductive film was also at 1721 cm-1. -1 1665cm -1 Two C=O vibration absorption peaks appeared at 3340cm -1 The OH vibration absorption peak appears at , indicating that the modified carbon nanotubes are successfully grafted onto the PVB film.

[0037] Preparation of high light transmittance dimming film:

[0038] The polymer dispersed liquid crystal is uniformly coated on the side of the transparent conductive film having the conductive layer, and then the side of another transparent conductive film having the conductive layer is covered on the polymer dispersed liquid crystal, and after ultraviolet light curing, a high-transmittance dimming film is obtained;

[0039] The components of the polymer dispersed liquid crystal include, by weight: 20 parts of 1,6-hexanediol di(meth)acrylate, 16 parts of 2-hydroxyethyl methacrylate, 30 parts of cholesteryl nonanoate, and 0.1 parts of photoinitiator UV-184.

[0040] Example 2

[0041] Preparation of transparent conductive film:

[0042] 10 parts of the modified carbon nanotubes obtained in Example 1, 0.1 parts of aluminum chloride, 0.5 parts of acetic acid, and 0.5 parts of sodium dodecyl sulfate were stirred in purified water for 5 minutes to form a suspension;

[0043] Then attach the transparent PVB film to the glass plate and then immerse them in the above suspension. The thickness of the suspension above the transparent PVB film is 2 mm. The ultraviolet light intensity is 5000 μW / cm2 and the irradiation time is 30 min. Under the action of microwaves, react for 3 hours and control the temperature at 40-55°C. Then take out the transparent PVB film and rinse it with water to obtain a transparent conductive film.

[0044] The high light transmittance dimming film is prepared by the method of Example 1.

[0045] Example 3

[0046] Preparation of transparent conductive film:

[0047] 15 parts of the modified carbon nanotubes obtained in Example 1, 0.1 parts of aluminum chloride, 0.5 parts of acetic acid, and 0.5 parts of sodium dodecyl sulfate were stirred in purified water for 5 minutes to form a suspension;

[0048] Then attach the transparent PVB film to the glass plate and then immerse them in the above suspension. The thickness of the suspension above the transparent PVB film is 2 mm. The ultraviolet light intensity is 5000 μW / cm2 and the irradiation time is 30 min. Under the action of microwaves, react for 3 hours and control the temperature at 40-55°C. Then take out the transparent PVB film and rinse it with water to obtain a transparent conductive film.

[0049] The high light transmittance dimming film is prepared by the method of Example 1.

[0050] Example 4

[0051] Preparation of transparent conductive film:

[0052] The raw materials are calculated by weight. 100 parts of amino carbon nanotubes, 0.5 parts of DMAP, and 20 parts of triethylamine are added to dichloromethane and mixed. 20 parts of N-chloroformyl-2-imidazolidinone are added dropwise under continuous stirring. The mixture is reacted for 2 hours. The mixture is filtered, washed with ethanol 3 times, washed with water 3 times, and vacuum dried at 50°C for 5 hours to obtain modified carbon nanotubes. The remaining methods are the same as in Example 1 to obtain a transparent conductive film.

[0053] The high light transmittance dimming film is prepared by the method of Example 1.

[0054] Example 5

[0055] Preparation of transparent conductive film:

[0056] The raw materials are calculated by weight. 60 parts of amino carbon nanotubes, 0.5 parts of DMAP, and 20 parts of triethylamine are added to dichloromethane and mixed. 50 parts of N-chloroformyl-2-imidazolidinone are added dropwise under continuous stirring. The mixture is reacted for 2 hours. The mixture is filtered, washed with ethanol 3 times, washed with water 3 times, and vacuum dried at 50°C for 5 hours to obtain modified carbon nanotubes. The remaining methods are the same as in Example 1 to obtain a transparent conductive film.

[0057] The high light transmittance dimming film is prepared by the method of Example 1.

[0058] Example 6

[0059] The transparent conductive film is prepared by the method of Example 1.

[0060] Preparation of high light transmittance dimming film:

[0061] Place the side of the transparent conductive film with the conductive layer upward, then align the micro-nano imprint template with the transparent conductive film and put it into the imprinting machine, perform imprinting at 60°C and 3MPa pressure, maintain the pressure for 5 minutes, then cool and demold to obtain a horizontal alignment layer, and then coat the polymer dispersed liquid crystal;

[0062] The side of another transparent conductive film with a conductive layer is also copied using the above-mentioned micro-nano imprinting technology to obtain a horizontal alignment layer, which is then covered on the polymer dispersed liquid crystal and cured to obtain a high-transmittance dimming film. The high-transmittance dimming film is a reverse dimming film.

[0063] Comparative Example 1

[0064] N-chloroformyl-2-imidazolidinone was replaced by p-chloroacetophenone, and the rest of the method was the same as in Example 1.

[0065] Comparative Example 2

[0066] The PVB resin and the modified carbon nanotubes obtained in Example 1 were mixed uniformly, and then a conductive film with a thickness of 100 μm was obtained by a casting method.

[0067] It should be noted that the raw materials are calculated in parts by weight, and the ratio of PVB resin to modified carbon nanotubes is the same as the ratio of transparent PVB film to modified carbon nanotubes in Example 1.

[0068] Comparative Example 3

[0069] The transparent PVB film was replaced with a PET film, and the rest of the method was the same as in Example 1 to obtain a conductive film.

[0070] The polymer dispersed liquid crystal obtained in Example 1 is uniformly coated on one side of the transparent conductive film having a conductive layer, and then another transparent conductive film having a conductive layer is covered on the polymer dispersed liquid crystal. After UV curing, a high-transmittance dimming film is obtained.

[0071] The initial square resistance and the square resistance of the conductive film when bent 500 times with a curvature of 1 cm were tested by a four-probe method, the transmittance of the conductive film was tested by a transmittance tester, and the 180° peel strength of the conductive film was tested by using a tensile testing machine.

[0072] The sources of the above raw materials are as follows:

[0073] Transparent PVB film: Shanghai Yueke New Materials Co., Ltd., thickness 100μm, light transmittance 93%;

[0074] PVB resin: Shanghai Yueke New Materials Co., Ltd., raw material for transparent PVB film;

[0075] Aminated carbon nanotubes: Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., catalog number XFS14;

[0076] N-chloroformyl-2-imidazolidinone: Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS No.: 13214-53-4;

[0077] p-Chloroacetophenone: Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 99-91-2;

[0078] DMAP (4-dimethylaminopyridine): Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 1122-58-3;

[0079] Aluminum chloride: Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 7446-70-0;

[0080] Acetic acid: Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 64-19-7;

[0081] Sodium dodecyl sulfate: Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 151-21-3;

[0082] Cholesteryl nonanoate: Shanghai Myrel Biochemical Technology Co., Ltd., CAS No.: 1182-66-7;

[0083] 1,6-Hexanediol di(meth)acrylate: Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 6606-59-3;

[0084] 2-Hydroxyethyl methacrylate: Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 868-77-9;

[0085] Photoinitiator UV-184: Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 947-19-3.

[0086] Results test:

[0087] The test results of the conductive film performance of the above embodiments and comparative examples are shown in Table 1 below:

[0088]

[0089]

[0090] The driving voltage, foggy state transmittance and transparent state transmittance of the dimming films of the above embodiments and comparative examples were tested. The test results are shown in Table 2 below:

[0091] project Driving voltage / V Fog light transmittance / % Transparent state transmittance / % Example 1 36 4.7 87 Example 2 32 6.6 85 Example 3 25 6.8 84 Example 4 40 5.1 88 Example 5 47 4.5 86 Example 6 43 6.5 82 Comparative Example 1 68 6.3 83 Comparative Example 2 \ \ \ Comparative Example 3 \ \ \

[0092] It can be seen from Table 1 above that the transparent conductive film provided by the present invention, the modified carbon nanotubes obtained by grafting N-chloroformyl-2-imidazolidinone, has excellent conductivity and high transmittance, and after being bent 500 times, the conductivity does not change significantly, has high flexibility, and is suitable for making flexible dimming films.

[0093] As can be seen from Table 2 above, the dimming film provided by the present invention has a lower driving voltage, good fog-state shielding, and higher transparency in a transparent state. Among them, the positive dimming films obtained in Examples 1-5 are foggy when not powered on and transparent when powered on, and are suitable for places that require long-term light shielding, such as the sunroof of a car; the reverse dimming film obtained in Example 6 uses micro-nano embossing copy technology to form parallel micron-level grooves on the surface of the transparent conductive film, align the initial state of the liquid crystal molecules, and are transparent when not powered on and foggy when powered on. It is suitable for places that need to be transparent most of the time, such as car door glass.

[0094] The invention provides a modified carbon nanotube by acylation reaction between the chloroformyl part of N-chloroformyl-2-imidazolidinone and the amino group of the aminated carbon nanotube to form an amide bond.

[0095] N-chloroformyl-2-imidazolidinone is an alkyl ketone, and the modified carbon nanotubes contain carbonyl groups. Under the irradiation of ultraviolet rays, they will be excited to the singlet state. Subsequently, the unstable singlet molecules release energy and quickly jump to the relatively stable triplet state. In the transparent PVB film, the PVB molecular structure contains hydrogen-donating groups such as hydroxyl, acetyl and aldehyde groups. The carbonyl groups in the triplet molecules react with the hydroxyl groups of the PVB molecules through nucleophilic addition reaction, and the modified carbon nanotubes are grafted onto the surface of the transparent PVB film to obtain a transparent conductive film.

[0096] A person skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of protection of the present application is limited to these examples. In line with the concept of the present application, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present application as described above, which are not provided in detail for the sake of simplicity.

[0097] One or more embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present application should be included in the protection scope of the present application.

Claims

1. A transparent conductive film, characterized in that: The transparent conductive film comprises a transparent PVB film and a conductive layer formed by modified carbon nanotubes grafted on the surface of the transparent PVB film.

2. The transparent conductive film according to claim 1, characterized in that: The modified carbon nanotubes are products of acylation reaction between amino carbon nanotubes and N-chloroformyl-2-imidazolidinone.

3. The transparent conductive film according to claim 2, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: The raw materials are calculated by weight, and 50-110 parts of amino carbon nanotubes, 0.5-1 part of DMAP, and 10-50 parts of triethylamine are added to an organic solvent and mixed. 10-60 parts of N-chloroformyl-2-imidazolidinone are added under continuous stirring. After the reaction is complete, the modified carbon nanotubes are obtained by filtering, washing, and drying.

4. The transparent conductive film according to claim 3, characterized in that: The diameter of the amino carbon nanotube is 1-2 nm and the length is 5-30 μm.

5. The transparent conductive film according to claim 3, characterized in that: The organic solvent is at least one of dichloromethane, DMSO and DMF.

6. The transparent conductive film according to claim 1, characterized in that: The thickness of the conductive layer in the transparent conductive film is 10 to 55 nm.

7. A method for preparing a transparent conductive film according to any one of claims 2 to 6, characterized in that: The following steps are involved: Raw materials are measured in parts by weight; 5-15 parts of modified carbon nanotubes, 0.1-1 parts of aluminum chloride, 0.1-1 parts of acetic acid, and 0.1-1 parts of sodium dodecyl sulfate are stirred in water to form a suspension; Firstly, a transparent PVB film is attached to a substrate, and then both are immersed in the above suspension, irradiated with ultraviolet light for 10-60 minutes, and reacted under microwave for 2-10 hours. After that, the transparent PVB film and the substrate are taken out, and washed with water to obtain a transparent conductive film.

8. A high light transmittance dimming film, characterized in that: The invention comprises the transparent conductive film according to any one of claims 1 to 7, a polymer dispersed liquid crystal layer and the transparent conductive film according to any one of claims 1 to 7 which are stacked in sequence.

9. A high light transmittance dimming film, characterized in that: The invention comprises the transparent conductive film according to any one of claims 1 to 7, a horizontal alignment layer, a polymer dispersed liquid crystal layer, a horizontal alignment layer and the transparent conductive film according to any one of claims 1 to 7 which are stacked in sequence.

10. A method for preparing a high light transmittance dimming film according to claim 8 or 9, characterized in that: The preparation method comprises the following steps: A polymer dispersed liquid crystal is coated on one side of a transparent conductive film having a conductive layer, and then another side of a transparent conductive film having a conductive layer is covered on the polymer dispersed liquid crystal, and after curing, a high-transmittance dimming film is obtained; or The preparation method comprises the following steps: A micro-nano imprint copying technique is used on one side of the transparent conductive film having a conductive layer to form parallel distributed micron-scale grooves to obtain a horizontal alignment layer, and then a polymer dispersed liquid crystal is coated; The side of the other transparent conductive film with a conductive layer is also copied by micro-nano imprinting technology to form horizontal nano-scale grooves to obtain a horizontal alignment layer, which is then covered on the polymer dispersed liquid crystal and cured to obtain a high-transmittance dimming film; The method for preparing the horizontal alignment layer comprises the following steps: Place the conductive layer side of the transparent conductive film upwards, align the micro-nano imprint template with the transparent conductive film and place it in the imprinting machine, perform imprinting at 60-70°C and 2-6MPa pressure, maintain the pressure for 5-10 minutes, cool it down, demold it, and obtain a horizontal alignment layer.